Why I Am Not SHY: A Reply to Tononi and Cirelli - Marcos Gabriel Frank (Neural Plasticity)
In a recent article I reviewed an influential theory of sleep function, the “synaptic homeostasis hypothesis (SHY.)” According to SHY, sleep renormalizes synapses that are potentiated during prior wakefulness. I concluded that while SHY is a seminal theory with important implications about sleep function and the brain, its underlying mechanisms are poorly defined. In an accompanying article, the authors of SHY responded at length. Their reply is thoughtful and provocative, but unfortunately many of the points I raised were not accurately represented or addressed. In this brief commentary, I attempt to clarify some points of confusion. I also explain why any theory of sleep function is incomplete without an understanding of the underlying cellular mechanisms.